1992
DOI: 10.1093/clinchem/38.8.1491
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Measurement of Cortisol in Serum and Saliva After Different Forms of Cortisol Administration

Abstract: To prove the clinical usefulness of cortisol measurements in saliva for the exact assessment of a patient's corticoid status under therapeutic hormone substitution, we measured simultaneously total cortisol in serum and non-protein-bound cortisol in saliva after administration of different forms of hydrocortisone (cortisol) in eight cortisol-suppressed, healthy male volunteers. The intravenous and oral administration of 20 mg of cortisol exceeds the binding capacity of the corticosteroid-binding globulin (CBG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
45
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(52 citation statements)
references
References 0 publications
5
45
0
2
Order By: Relevance
“…Similar difficulties with early samples following oral administration have been reported previously. 18 After oral administration, elimination half-lives were shorter in saliva compared to plasma in 12 of 18 patients and similar or longer in three patients. These results were consistent with the observations of Tunn et al .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similar difficulties with early samples following oral administration have been reported previously. 18 After oral administration, elimination half-lives were shorter in saliva compared to plasma in 12 of 18 patients and similar or longer in three patients. These results were consistent with the observations of Tunn et al .…”
Section: Discussionmentioning
confidence: 88%
“…These results were consistent with the observations of Tunn et al . 18 who found that elimination half-life was shorter in saliva (66 min) compared to plasma (108 min) in eight healthy volunteers. This apparent initial faster decline in saliva compared to plasma may indicate that an additional route of elimination is available for salivary measurements, such as metabolism in the salivary glands.…”
Section: Discussionmentioning
confidence: 99%
“…19 A similar relationship has been also demonstrated following oral and intravenous administration of hydrocortisone. 20 Based on patients with responses in SerC >500 nmol/l, a value for an adequate response in SalC was established. Apart from the two patients with CBG deficiency, all patients who had inadequate SerC responses also had inadequate peak SalC values in both the dynamic tests studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is the free level that is sensed and regulated by the corticotrophin (CRH) -ACTH axis. Normal CBG has a cortisol-binding capacity of approximately 25 µg /dl; increases in total plasma cortisol concentrations above 550 nmol / l exceed the binding capacity of CBG and result in rapid increases in levels of free cortisol concentration ( Tunn et al, 1992). The cortisol-binding capacity of albumin is greater than that of CBG, but its affinity is lower.…”
Section: Discussionmentioning
confidence: 99%